Anal incontinence and unrecognized anal sphincter injuries after vaginal delivery- a cross-sectional study in Norway - Matilde Risopatron Berg; Ylva Sahlin (BMC, 2020)
Abstract Background Aim of the study was to estimate the prevalence of postpartum anal incontinence among women who delivered vaginally, and to assess the extent to which obstetric injuries to the anal sphincters are missed. Methods All women (both primiparous and multiparous) who delivered vaginally and received any kind of sutures in the perineal area at Innlandet Hospital Trust Elverum in Norway between January 1, 2015 and June 30, 2016 were invited to answer a questionnaire on St. Mark's incontinence score and to participate in a clinical examination of the pelvic floor including endoanal sonography. Results In total 52,3% (n = 207) of the 396 invited women participated in the study. Mean St. Mark's score was 1.8 points (95% CI 1.4 to 2.1) at examination 14 months (mean) postpartum, and none of the participants suffered from weekly fecal leakage. Fecal urgency affected 11.7% (95% CI 7.1 to 16.3) of the participants, and 8.7% (95%CI 5.1 to 12.8) had weekly involuntary leakage of flatus. Nine women (9.3%, 95% CI 4.1 to 15.5) had a previously undetected third degree obstetric anal sphincter injury. Conclusion The prevalence of anal incontinence among women who have delivered vaginally and received sutures due to 1st and 2nd degree perineal lacerations is low. Some obstetric anal sphincter injuries remain unrecognized at the time of delivery, but the symptoms of anal incontinence due to these injuries are in the lower half of the St. Mark's incontinence score. Women with persistent symptoms like fecal urgency or leakage of gas and/or feces should be referred to evaluation by a colorectal surgeon in order to achieve optimal treatment.